Jiedu Tongluo Granules Ameliorates Post-stroke Depression Rat Model via Regulating NMDAR/BDNF Signaling Pathway - Zhao, Aimei; Ma, Bo; Xu, Li; Yao, Mingjiang; Zhang, Yehao; Xue, Bingjie; Ren, Junguo; Chang, Dennis; Liu, Jianxun (Frontiers in Pharmacology, 2021)
Post-stroke depression (PSD) is one of the most common stroke complications, which seriously affects stroke's therapeutic effect and brings great pain for patients. The pathological mechanism of PSD has not been revealed. Jiedu Tongluo granules (JDTLG) is an effective traditional Chinese medicine for PSD treatment which is widely used in clinical treatment. JDTLG has a significant therapeutic effect against PSD, but the mechanism is still unclear. The PSD rat model was established by carotid artery embolization combined with chronic sleep deprivation followed by treating with JDTLG. Neurobehavioral and neurofunctional experiments were engaged in studying the neural function of rats. Histomorphology, proteomics, and western blotting researches were performed to investigate the potential molecular mechanisms related to JDTLG therapy. Oral treatment of JDTLG could significantly improve the symptoms of neurological deficit and depression symptoms of PSD rats. Proteomic analysis identified several processes that may involve the regulation of JDTLG on the PSD animal model, including energy metabolism, nervous system, and N-methyl-D-aspartate receptor (NMDAR)/ brain-derived neurotrophic factor (BDNF) signal pathway. Our results showed that JDTLG could reduce glutamate (Glu) level and increase gamma-aminobutyric acid (GABA) level via regulating the NMDAR/BDNF pathway, which may play a vital role in the occurrence and development of PSD.